Strategi Bimbingan Karier Dengan Teknik Modeling di SMK Muhammadiyah Kota Cirebon - Akhirani, Shinta Tiresa; Maesaroh, Siti; Marwanto, Marwanto; Kuat, Tri (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to: (1) analyze the strategies for implementing career guidance using modeling techniques at SMK Muhammadiyah Kota Cirebon; (2) identify the obstacles encountered in the implementation of career guidance strategies using modeling techniques; and (3) examine the benefits of implementing these strategies for students in career planning. This research employed a qualitative method with a descriptive approach. The research subjects consisted of the principal, guidance and counseling teachers, and 10 students of SMK Muhammadiyah Kota Cirebon who participated in career guidance services. Data were collected through in-depth interviews to obtain a comprehensive understanding of the strategies for implementing career guidance using modeling techniques. The results indicate that career guidance strategies using modeling techniques are effective in bridging students’ readiness from the school environment to the world of work and professional life in a more mature manner. The obstacles identified include limited time for coordination with industry partners, the need to update practical facilities, and differences in students’ characteristics. To address these challenges, the school has undertaken various efforts, such as strengthening internal coordination, providing individual guidance, and improving facilities that support career guidance services. The benefits of implementing this strategy include increased self-understanding, enhanced career knowledge, improved motivation, and greater readiness among students in planning their future careers.